Digital Onboarding in Agricultural Platforms and its Impact on Agricultural Productivity - Sunarjo, Richard Andre; Pujiati, Tri; Apriliasari, Dwi; Hardini, Marviola (IAIC Transactions on Sustainable Digital Innovation (ITSDI), 2025)
This study explores the transformative role of digital onboarding in the agricultural sector, emphasizing its potential to bridge the digital divide, enhance productivity, and promote sustainability. By integrating advanced technologies such as Artificial Intelligence (AI), blockchain, and the Internet of Things (IoT), digital onboarding provides a pathway for stakeholders to adopt precision agriculture. It also helps overcome key obstacles such as limited digital skills and unequal access to tools or infrastructure. The research extends digital ecosystem theory by framing onboarding as a practical pathway for building inclusive and resilient farming systems. It highlights the importance of integrating technological innovations with policy frameworks and capacity building initiatives to ensure equitable benefits for smallholder farmers and marginalized groups. A qualitative and analytical approach was employed, synthesizing insights from scientific literature, case studies, and expert reviews. The study examines global agricultural digital platforms such as Estagrx to evaluate the effectiveness of digital onboarding strategies in diverse geographical and socio- economic contexts. Findings reveal that digital onboarding strengthens agricultural system robustness by enhancing stakeholder engagement, improving supply chain transparency, and optimizing resource utilization. Additionally, it supports sustainable agricultural practices through precision techniques that reduce wastage and conserve resources. The study concludes that addressing barriers such as cultural resistance and socioeconomic disparities requires collaborative efforts among governments, private sectors, and international organizations to scale digital solutions for agriculture effectively.